Global burden of Hodgkin lymphoma among children and adolescents: a population-based study using GBD 2021 - Chen, Jie; Wang, Yue; Guo, Jindou; Song, Yuqin; Zhu, Jun; Ma, Jun; Zhou, Maigeng; Qi, Jinlei; Liu, Weiping (Frontiers in Pediatrics, 2025)
BackgroundHodgkin Lymphoma is a rare lymphatic system malignancy which has a negative impact on the health of children and adolescents. While high-income regions have seen a decline in mortality rates due to early diagnosis and advances in treatment strategies (e.g., chemotherapy, radiotherapy, and targeted therapy), low- and middle-income countries continue to face high mortality rates due to limited medical resources and delayed treatment.MethodsEmploying data from the Global Burden of Disease (GBD) 2021 study, this analysis assessed the burden of Hodgkin lymphoma among children and adolescents from 1990 to 2021. Metrics including incidence, mortality, and disability-adjusted life years (DALYs) were evaluated across Socio-demographic Index (SDI) quintiles. Age-Period-Cohort (APC) and Nordpred models were used to analyze long-term trends and project future disease burden. Additionally, joinpoint regression analysis identified significant temporal shifts in trends throughout the study period.ResultsThe estimated DALY number was 265,016, and the ASDR among children and adolescents was 9.816 per 100,000 person in 2021. There were 8,700 new HL cases and 3,385 deaths, and the ASIR and ASMR were 0.320 and 0.125 per 100,000 population, respectively. The estimated number of prevalent HL cases was 50,128 worldwide with the ASPR of 2.001 per 100,000 population. Globally, the Hodgkin lymphoma burden was consistently higher in male children and adolescents than in females across all metrics. Results reveal a global decline in age-standardized incidence rates of HL among children and adolescents, with significant regional variations. Low- and middle-income regions experienced an increase in HL burden, while high-income regions showed a decline trend. The case number of HL in the children and adolescents increased from 8,283 in 1990 to 8,700 in 2021, while ASIR declined by 9.52%. The APC model projected a continued decline in HL incidence and mortality globally by 2040. However, health inequalities persist, with low-income countries bearing a disproportionately high burden of HL.ConclusionsThe burden of HL among children and adolescents is increasing, with a significant difference by sex, age and regions, which highlight the urgent need for equitable diagnostic and therapeutic access in low-resource settings to meet the 2030 SDG targets on child health.